Complex Flavonoids of Pityrogramma trifoliata: Absolute Configuration, Antifungal Effects, and Localization in the Plant - Rodriguez, Ana María del Valle (2022)
Chemical investigation of the fern Pityrogramma trifoliata (L.) R. M. Tryon (Pteridaceae) yielded a new complex flavonoid, here named trifoliatol, and 4 known complex flavonoids in addition to known chalcones and flavanones. The absolute configuration of the complex flavonoids is proposed, based on circular dichroism (ECD), crystal x-ray diffraction, and [α]D measurements. White and yellow farinas, as well as 10 flavonoids were tested for antifungal activity against a panel of clinically important fungi, including yeast and dermatophytes. Both farinas and 2 of the flavonoids were notably active against Trichophyton rubrum and T. mentagrophytes (MICs and MFCs between 7.8 and 31.2 μg/mL). The localization of flavonoids in the plant trichomes was accomplished by use of scanning electron microscopy and histochemical methods.